Lady Louisa's Christmas knight - Burrowes, Grace (Burrowes, Grace. Windhams., 2012)
Years ago Lady Louisa Windham acted rashly on a dare from her brother, and that indiscretion is about to come to light. She knows her reputation will never survive exposure. Just as she's nearly overwhelmed by her dilemma, Sir Joseph Carrington offers himself to her as a solution..But Sir Joseph has secrets as well, and as he and Louisa become entangled with each other, their deceptions begin to close in on them both.